Handbook of clinical nutrition and stroke - Corrigan, Mandy L.; Escuro, Arlene A.; Kirby, Donald (Nutrition and health (Totowa, N.J.), 2013)
Handbook of Clinical Nutrition and Stroke is a comprehensive reference on nutrition for the multidisciplinary team caring for stroke patients. Targeting physicians, nurse practitioners, clinical dietitians, and advanced allied health and medical students, this volume provides an introduction on the different types of stroke, associated risk factors, and uniquely featured global perspectives on stroke. In addition to discussing stroke risk factors, the book expands upon treatment and management from the acute care setting through rehabilitation, captures the lifespan of patients affected by st.